No evidence that seaweed cover enhances the deterioration of natural‐cement‐based mortar in intertidal environments - Baxter, T; Coombes, M; Viles, H (Wiley, 2022)
The breakdown of rocks and engineering materials in marine environments is both enhanced and retarded by surface-colonizing marine organisms (seaweed, barnacles, etc.). However, the impact of marine growth on the deterioration of materials used to construct and repair maritime heritage assets, such as natural cement, is poorly understood. This study assesses whether seaweed cover (Fucus vesiculosus and Fucus serratus) influences the breakdown of mortar prepared using natural cement through an exposure trial at Portland Port, Dorset, UK. Using microclimate monitoring and three different indicators of weathering and material breakdown (surface hardness, surface roughness and ultrasonic pulse velocity), samples of mortar with and without a cover of seaweed were compared after 6 months of exposure to intertidal conditions. Our results show that temperature variations were significantly dampened under seaweed canopies compared to uncovered substrate both in summer and winter. As mechanical rock weathering processes are influenced by surface temperature regimes, we infer that these stabilizing effects may translate to a reduction in the efficacy of particular rock breakdown processes. Seaweed cover was not found to have significant effects on the surface hardness of the samples. Conversely, significant differences in surface roughness and pulse velocity were observed, indicating that the seaweed-covered samples experienced less surface and subsurface breakdown. Overall, we found no evidence that seaweed significantly enhances the deterioration of natural cement-based mortar during the first few months of exposure. Instead, we present the first empirical evidence of the bioprotective potential of seaweed covering materials commonly used in maritime built heritage restoration. Future work is now needed to examine the geomorphic roles of seaweed and other marine organisms on different types of materials used in maritime heritage conservation, and the extent to which their impacts on different deteriorative/protective processes vary in time and space, particularly under future climatic scenarios.